Bioactive strawberry fruit (Arbutus unedo L.) extract remedies paraquat-induced neurotoxicity in the offspring prenatally exposed rats - Ait Lhaj, Zakaria; Ibork, Hind; El Idrissi, Sara; Ait Lhaj, Farida; Sobeh, Mansour; Mohamed, Wael M. Y.; Alamy, Meryem; Taghzouti, Khalid; Abboussi, Oualid (Frontiers in Neuroscience, 2023)
Paraquat (1,1ʹ-dimethyl-4-4ʹ-bipyridinium dichloride) exposure is widely recognized as a neurotoxic agent that can result in neurological deficits in offspring. This study aimed to investigate the phytoconstituents (via LCMS), antioxidant potential, and therapeutic effects of Arbutus unedo L. aqueous extract (AU) against Paraquat (PQ) exposure by assessing its impact on cell viability and mitochondrial metabolism using N27 dopaminergic cells. Additionally, we evaluated the effects of prenatal PQ exposure on motor coordination, dopamine levels, trace element levels, and total antioxidant capacity (TAC) in rat progeny. The phytochemical profile of AU extract revealed the presence of 35 compounds, primarily phenolic and organic acids, and flavonoids, which accounts for its strong in vitro antioxidant activities against DPPH (2,2-diphenylpicrylhydrazyl) and ABTS (2,2'azino-bis (3-ethylbenzothiazoline-6-sulfonic acid)) radicals (IC50 of 5.089 ± 0.221 and 11.55 ± 0.1634 µg/ml, respectively), compared to the activities of vitamin C (IC50 of 2.799 ± 0.031 and 5.900 ± 0.1832 µg/ml, respectively). Our findings demonstrated that AU effectively inhibits PQ-induced loss of N27 rat dopaminergic neural cells and significantly enhances their mitochondrial respiration. Furthermore, daily posttreatment with AU during the 21 days of the rat's pregnancy alleviated PQinduced motor deficits and akinesia in rat progeny. These effects inhibited dopamine depletion and reduced iron levels in the striatal tissues. The observed outcomes appeared to be mediated by the This is a provisional file, not the final typeset article robust antioxidant activity of AU, as it effectively counteracted the PQ-induced decrease in TAC in the blood plasma of rat progeny. These effects could be attributed to the bioactive compounds present in AU, including phenolic acids such as gallic acid and flavonoids such as quercetin, rutin, apigenin glucuronide, and kaempferol, all of which are known for their potent antioxidant capacity. In conclusion, this preclinical study provided the first evidence of the therapeutic potential of AU extract against PQ-induced neurotoxicity. These findings emphasized the need for further exploration of AU's clinical applicability in mitigating neurotoxin-induced brain damage.